Finance-specific Factors as Drivers of Cross-border Investment: An OLI Perspective - Jens Forssbaeck; Lars Oxelheim (Research Institute of Industrial Economics (IFN), 2008)
In this paper we empirically test the role of firm-specific financial characteristics as drivers of international investment and production. We hypothesize that financial strength generates advantages that can be exploited through cross-border investment activity. The hypothesis is tested in a series of binary-response models, using a sample of 1379 European non-financial firms international acquisitions. Controlling for traditional firm- and target-country-specific FDI determinants within an OLI framework, we find strong evidence that financial factors play a significant role in explaining cross-border investment. We conclude that without explicit consideration of the financial dimension, firms FDI decisions cannot be properly understood.
Keywords: E22; F21; F23; L23; 330; FDI; OLI; Cross-border Acquisitions; Cost of Capital; Financial Strategy; Financial Variables; Direktinvestition; Multinationales Unternehmen; Übernahme; Kapitalkosten; Kapitalstruktur; EU-Staaten